Chemical Synthesis and Semisynthesis of Lipidated Proteins. Issue 15 (3rd February 2022) - Hanna, Cameron C.; Kriegesmann, Julia; Dowman, Luke J.; Becker, Christian F. W.; Payne, Richard J.
Abstract: Lipidation is a ubiquitous modification of peptides and proteins that can occur either co‐ or post‐translationally. An array of different lipid classes can adorn proteins and has been shown to influence a number of crucial biological activities, including the regulation of signaling, cell–cell adhesion events, and the anchoring of proteins to lipid rafts and phospholipid membranes. Whereas nature employs a range of enzymes to install lipid modifications onto proteins, the use of these for the chemoenzymatic generation of lipidated proteins is often inefficient or impractical. An alternative is to harness the power of modern synthetic and semisynthetic technologies to access lipid‐modified proteins in a pure and homogeneously modified form. This Review aims to highlight significant advances in the development of lipidation and ligation chemistry and their implementation in the synthesis and semisynthesis of homogeneous lipidated proteins that have enabled the influence of these modifications on protein structure and function to be uncovered. Abstract : Lipidation is a co‐ and post‐translational modification that is known to influence the structure, function, and localization of peptides and proteins. This Review aims to highlight significant advances in the development of modern synthetic and semisynthetic methods for the generation of homogeneously lipidated proteins that have underpinned the study of the effects of lipid modifications on protein structure and function with unprecedented precision.